2016
DOI: 10.1371/journal.pone.0164894
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Fecal Soap Fatty Acids, Calcium Contents, Bacterial Community and Short-Chain Fatty Acids in Sprague Dawley Rats Fed with Different sn-2 Palmitic Triacylglycerols Diets

Abstract: The structure of dietary triacylglycerols is thought to influence fatty acid and calcium absorption, as well as intestinal microbiota population of the host. In the present study, we investigated the impact of palmitic acid (PA) esterified at the sn-2 position on absorption of fatty acid and calcium and composition of intestinal microorganisms in rats fed high-fat diets containing either low sn-2 PA (12.1%), medium sn-2 PA (40.4%) or high sn-2 PA (56.3%), respectively. Fecal fatty acid profiles in the soaps we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Meanwhile, fatty acid distribution in human milk TG are not random. Over 70% of the palmitic acid is esterified at the second (sn-2) carbon of the TG glycerol backbone, which reduces extraction of fecal soap fatty acids and calcium malabsorption, and promotes early bone mineralization (Wan et al, 2016;Miles and Calder, 2017). Thus, in human milk, not only the species of TG but also the regioisomers and enantiomers of TG play important nutritional and physiological Regioisomeric and enantiomeric analysis of primary triglycerides in human milk by silver ion and chiral HPLC atmospheric pressure chemical ionization-MS roles.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, fatty acid distribution in human milk TG are not random. Over 70% of the palmitic acid is esterified at the second (sn-2) carbon of the TG glycerol backbone, which reduces extraction of fecal soap fatty acids and calcium malabsorption, and promotes early bone mineralization (Wan et al, 2016;Miles and Calder, 2017). Thus, in human milk, not only the species of TG but also the regioisomers and enantiomers of TG play important nutritional and physiological Regioisomeric and enantiomeric analysis of primary triglycerides in human milk by silver ion and chiral HPLC atmospheric pressure chemical ionization-MS roles.…”
Section: Introductionmentioning
confidence: 99%
“…Among the nutrients in these seeds, lipid is one of the most important components, which contains more than 95% triacylglycerols (TAGs) [ 5 , 8 ]. Recently, increasing evidence has demonstrated that not only the fatty acid compositions, but also their binding positions in TAGs play very important roles in the functionality and nutrition values of seed oils [ 9 , 10 , 11 , 12 ]. For example, binding positions of fatty acids to TAG altered their oxidative stability, calcium absorption, and lipid metabolism [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies had showed that intake of dietary lipids which was rich in TAGs with palmitic acid at sn-2 positions could effectively decrease the fecal Ca, total lipids, and palmitic acid content. Moreover, it also had positive effects for maintaining the gut homeostasis (Miles & Calder, 2017;Wan et al, 2016), confirming that the composition of the dietary oil could influence the nutrients bioavailability by modulating the gut homeostasis. The gut dysbiosis in turn exacerbated the malabsorption of the nutrients, and affected the host health, as similarly displayed in the present research.…”
Section: F I G U R Ementioning
confidence: 83%
“…Folch method was used to extract the total lipids in the fecal samples (Folch et al, 1957). All the samples were pretreated according to the previous studies with some modifications (Shang et al, 2017;Wan et al, 2016). Briefly, accurately weighing about 80 mg of frozen feces sample into the Eppendorf test tube, followed by 800 μl normal saline.…”
Section: Analysis Of the Fatty Acid Composition In The Fecal Samplesmentioning
confidence: 99%